Analysis Of Factors Effecting The Firm Value Factors That Effect The Firm Value - Ni Made Sunarsih; Ni Putu Shinta Dewi; Monica Ni Nyoman Aprilia Kireina (International Journal of Applied Business and International Management, 2019)
Company value was a picture of a company in certain condition that they want to achieve as a form of trust from people to the company. The long term goals that they have when they start a company was to increase the value of the company, and to increase the prosperity of their owner and stakeholder. The higher the price of a stock company, shows that the higher profit that the stakeholder gets, and shows the value of a company is rising. In this research value of company can proxied by Price to Book Value (PBV) This study aims to determine the Effect of Corporate Social Responsibility and Intellectual Capital on the Value of Manufacturing Companies Listed on the Indonesia Stock Exchange (IDX) during the period 2015-2017. The total sample of this study is 204 manufacturing companies listed on the Indonesia Stock Exchange in 2015-2017. Determination of samples using purposive sampling method. The analysis technique used is multiple linear analysis. The results of this study indicate that the variables of Corporate Social Responsibility and Intellectual Capital have a positive effect on firm value (PBV).